Analysis of sesame phyllody disease using transmission electron microscopy and intersimple sequence repeat-polymerase chain reaction - Haj Ali, Mayadah A.; Kheder, Ahmed A.; Hamwieh, Aladdin (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Sesame phyllody disease caused by phytoplasma has been identified in Egypt as a devastating phytopathogenic mollicute, However, the genetic diversity of phytoplasma infecting sesame plants in Egypt, as revealed by Intersimple Sequence Repeats-Polymerase Chain Reaction (ISSRs-PCR), has not been fully explored. During 2021–2022, sesame plants exhibiting virescence, phyllody, proliferation, and witches’ broom symptoms were observed in various fields across the Faiyoum, Luxor, and Beheira governorates in Egypt. This study aims to identify phytoplasma using transmission electron microscopy (TEM) and ISSRs-PCR. The methodology includes sampling, pathogenicity testing, TEM analysis of ultrathin sections, nested polymerase chain reaction (nested-PCR) targeting the 16S rRNA gene, and clustering analysis using 15 ISSRs primers. Phytoplasma was successfully transmitted to healthy plants through grafting and dodder transmission, with success rates of 80% and 90%, respectively. TEM analysis revealed polymorphic phytoplasma bodies and extensive phloem necrosis. Nested-PCR produced 1250 bp amplicons for all isolates. Phylogenetic analysis showed that the Beheira isolate (“OP185273.1”) is closely related to the peanut WB group. DNA polymorphic fragments ranged from 1 to 10 per profile, with fragment sizes between 150 and 1500 bp. Cluster analysis revealed that only two isolates (Faiyoum and Beheira) clustered together. This study demonstrates the effectiveness of ISSR-PCR in detecting and analyzing phytoplasma infecting sesame plants in Egypt.